Rat and Mouse Control - P.G. Koehler; W.H. Kern, Jr. (EDIS)
Rats and mice are important rodent pests entering Florida homes and warehouses for food and harborage. These rodents eat any kind of food that people eat. They also contaminate 10 times as much food as they eat, with urine, droppings and hair. They can carry at least 10 different kinds of diseases including bubonic plague, murine typhus, spirochetal jaundice, Leptospirosis, rabies, ratbite fever, and bacterial food poisoning. This document provides information about rats and mice: how to recognize them, feeding habits and behavior, as well as methods to eradicate them. First published in June, 1991.